LIVING TOWER CONSTRUCTION AS FISH APARTMENT WITH GLASS POWDER/PET COMPOSITE BASIC TECHNOLOGY - Dioktyanto, Mudzakkir; Jati, Aditya Damar; Purwaningsih, Hariyati; Kusumawati, Monica Gayatri; Fanani, Yordan; Falah, Muhammad Afni Nadzir (MATTER: International Journal of Science and Technology, 2017)
Inorganic waste cannot decompose easily by nature, plastic bottles takes about 50-100 years while the glass bottle takes about 1 million years. At the moments, it will causes serious contamination into soil, water, or air if not treated properly. In addition, Indonesia has a coral reefs area reaching about 18% of the world coral reefs area. Fish populations and other marine biota Lived In coral reefs and recorded 2,200 or 31% species of reef fish in the world are in Indonesian waters. However, water pollution is the reason for about 70% of damaged coral reefs. Living Tower as a fish apartment made from glass and plastic bottle waste can overcome the amount of garbage that accumulates and provides a home for the existing marine fish population. Living Tower design has a unique shape, in which this Living Tower has 4 structural building poles around it made from glass powder/ PET composite technology with melting processes arranged so as to suit marine conditions, and has a main pole as a gathering place for fish made from natural fibers as a place to attach fish eggs. Making Living Tower is able to reduce the waste of glass bottles, and plastic bottles as much as 6.6 kg for every 1 unit produced. From this research we have publication and patent. In the future this technology will be needed because waste around us must be utilized, and there are several research that discuss about making concrete from this composite.